A comprehensive review of corrosion protection and control techniques for metallic pipelines. (January 2023) - Farh, Hassan M. Hussein; Ben Seghier, Mohamed El Amine; Zayed, Tarek
Highlights: Comprehensive scientometric and systematic reviews of corrosion protection methods for metallic pipelines are detailed. 122 research articles are used to divide, classify, and discuss external and internal corrosion protection methods. The functions, limitations, and requirements of corrosion protection methods are reported and discussed. The purpose of this review is to assist researchers in filling research gaps and focusing on future directions. Abstract: Metallic pipelines carrying water and/or oil/gas are exposed to deterioration, leaks/bursts, and failures due to corrosion. A suitable corrosion protection technique can prevent corrosion of these metallic pipelines, particularly in hostile environments, and corrosive soils. It can also reduce pipe deterioration, leaks/breaks, and failure, prolong service life, and improve the transportation process. Based on prior studies, this comprehensive review is regarded as an early attempt to cover both external and internal corrosion protection techniques for metallic pipelines in depth. The external corrosion protection techniques are classified into passive, active and hybrid corrosion protection techniques. The passive techniques include coatings, linings, barriers, material design, electrical isolation, inhibitors, and multi-passive techniques. Whereas active corrosion protection techniques include sacrificial anode and impressed current cathodic protections. Active and passive techniques are frequently combined to provide a more comprehensive corrosion protection system against newly discovered corrosion causes or coating degradations. On the other hand, internal corrosion protection techniques include internal coatings/linings/barriers, corrosion allowance, inhibitors/chemical treatments, dehydration, pigging, pipe material selection and flow control. The functions, merits, demerits, limitations/shortcomings, and requirements of corrosion protection techniques, as well as the various considerations that control their use have been covered and discussed. This comprehensive review will assist researchers, practitioners, and the industrial sector in prioritizing their policies in order not only to select the appropriate external and internal corrosion protection technique but also to fill current research gaps and focus on the future directions.